Antibiotic prophylaxis in COPD: Why, when, and for whom?. (June 2015) - Miravitlles, Marc; Anzueto, Antonio
Abstract: One of the main goals of treatment of chronic obstructive pulmonary disease (COPD) is the prevention of exacerbations. Bronchodilators and anti-inflammatories are the first line therapy for treatment of COPD; however, these drugs are not effective in suppressing all infective exacerbations. In fact, the use of inhaled corticosteroids in patients with COPD and chronic bronchial infection may even increase the bacterial load in the airways and increase the risk of pneumonia. In this context, the use of long-term or intermittent antibiotic treatment has shown to prevent COPD exacerbations and hospitalizations. These effects may be achieved by reducing bacterial load in the airways in stable state and/or bronchial inflammation. The drugs more extensively studied are macrolides, followed by quinolones. The long-term use of antibiotics is associated with an increased risk of potentially serious adverse events and development of bacterial resistance. Therefore, the indication of long-term antibiotic therapy must be determined on a case by case basis taking into account the potential risks and benefits. In general, this treatment may be indicated in patients with severe or very severe COPD with frequent or severe exacerbations despite optimal pharmacological and non pharmacological treatment. These patients should be carefully monitored based on clinical and microbiological assessments. The most appropriate drug and regime administration, as well as the optimal duration of therapy are issues that still require further investigation.